On the method of precise abundance determination of isotopologues in a gas mixture: Effective dipole moment parameters for the fundamental bands of different isotopologues of H2O, H2S, H2Se, SO2, O3, H2CO, H2CS, and C2H4; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 242 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Bekhtereva E. S. Elena Sergeevna; Gromova O. V. Olga Vasilievna; Belova A. S. Anastasiya Sergeevna; Bauerekker (Bauerekker) Z. Kh. Zigurd Khermann (2020, 2020)
Title screen